Implementasi Pendekatan Diferensiasi dalam Mengoptimalkan Partisipasi Siswa Bidang Studi IPAS di SDN 03 - Mila Sari; Muhammad Ali Akbar (Kilau Publishing, 2025)
The low level of student engagement in IPAS learning at SDN 03 Kerangan Purun is a major issue that hinders the creation of an active and meaningful learning environment. One of the main causes is the use of conventional teaching methods that do not take into account the diverse characteristics, interests, and learning styles of students. The purpose of this study is to describe the implementation of a differentiated approach in enhancing the student engagement at SDN 03 Kerangan Purun, Sayan District, in the subject of IPAS. This study used the Classroom Action Research (CAR) method based on the Kemmis and McTaggart model, which consists of four main stages: planning, action implementation, observation, and reflection. The study involved 16 students as subjects, with diverse learning characteristics and preferences. Data was collected using observation, verbal interaction, and document review. The findings show a gradual optimization of student participation, with the level of engagement recorded at 31.25% during the pre-cycle stage. After the action was implemented in cycle I, the engagement increased to 62.5%. This increase continued in cycle II, where student engagement reached 81.25%. These findings suggest that the implementation of differentiated learning approaches has a positive impact on student participation in the classroom. The application of differentiated approaches tailored to students' interests, learning styles, and readiness has proven to create a more active and meaningful learning environment. In conclusion, differentiated learning is effective in enhancing student participation in IPAS learning at elementary schools.